Splint Duration and Not the Mode of Anesthesia Is the Main Factor Influencing Avascular Necrosis After Closed Reduction for Developmental Dysplasia of the Hip in Kosovo - Sllamniku, Sabit; Beqo, Besiana P.; Krasniqi, Islam; Tërshana, Azem; Murtezani, Ardiana; Quehenberger, Franz; Haxhija, Emir Q. (Frontiers in Pediatrics, 2022)
Abstract This study aimed to determine whether the use of analgesia and sedation (AS), as opposed to general anesthesia (GA) for closed reduction and spica casting of children with severe developmental dysplasia of the hip (DDH) influenced the long-term incidence of avascular necrosis (AVN). In a prospective, randomized, single-blinded clinical trial we investigated 100 pediatric patients with DDH type IIIa, IIIb, IV (according to Graf classification), who were randomly assigned into the group receiving AS, and the group receiving GA. Baseline demographics, splint duration and type of DDH were carefully assessed. The presence of AVN was assessed at the follow-up visits at 1 and 7 years after the end of treatment. The AS-group consisted of 50 patients (46 girls) with 76 hips affected (n=11/Type-IIIa, n=32/Type-IIIb, and n=33/Type-IV). The GA-group consisted also of 50 patients (44 girls) with 78 hips involved (n=15/Type-IIIa, n=34/Type-IIIb, and n=29/Type-IV). At 7-years follow-up, AVN was diagnosed in 9 of 154 hips (5.8%), 5 hips in the AS-group and 4 hips in the GA group, respectively. The logistic regression model showed no significant difference in AVN incidence between the AS and GA groups at 7-years follow-up (p=0.27). The multivariate regression analysis showed that neither the type of DDH, nor the age at diagnosis influenced the incidence of AVN (p=0.48 and p=0.28, respectively). Splint duration was identified as the only significant factor for the long-term incidence of AVN in the treatment of severe DDH. For every month of longer splint duration, the odds of AVN at 7-years follow-up increased by a factor of 3.81 (95%CI:1.35-13.73, p=0.02). Closed reduction and spica casting of children with severe DDH under AS can be considered a feasible alternative to management under GA. All efforts must be made to diagnose patients with DDH as early as possible and shorten the duration of splint treatment to prevent development of AVN. Level of Evidence. Level II-1